Between the devil and the deep blue sea: puerperal sepsis and pituitary apoplexy following obstetric hysterectomy for postpartum haemorrhage - K. K., Akshay Kumar; C. K., Ramesan; Vimalraj, Sajala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Sheehan’s syndrome, or postpartum pituitary necrosis, is a rare but life-threatening complication of severe postpartum hemorrhage (PPH). Its diagnosis is often delayed or obscured when confounded by concurrent critical illnesses. We report a case of acute Sheehan’s syndrome masked by severe puerperal sepsis to highlight the diagnostic challenges involved. A 38-year-old multiparous woman developed severe atonic PPH following a vacuum-assisted delivery, necessitating an emergency subtotal hysterectomy. Her postoperative course was complicated by severe sepsis, multi-organ dysfunction, and recurrent hypoglycaemia. Despite aggressive sepsis management, her condition remained critical. A pivotal diagnostic clue was her complete failure to lactate. Hormonal assays revealed panhypopituitarism (low follicle-stimulating hormone (FSH), luteinizing hormone (LH), thyroid-stimulating hormone (TSH), and cortisol), and a computed tomography (CT) scan of the brain confirmed an empty sella. The patient stabilized only after the initiation of hormone replacement therapy (hydrocortisone and thyroxine). Sheehan’s syndrome should be suspected in any patient with a history of severe PPH who presents with non-specific signs of critical illness, particularly refractory hypoglycaemia and failure to lactate. Concomitant sepsis can mask these features, delaying diagnosis. Early recognition and multidisciplinary management are essential for survival.